Noniterative feedback midcourse guidance for exo-atmospheric interception of ballistic targets using virtual impact point steering - Jo, Byeong-Un; Ahn, Jaemyung (Aerospace science and technology, 2021)
This paper proposes a noniterative feedback midcourse guidance algorithm for intercepting a ballistic target. The virtual impact point (VIP) concept, which is the intersection point between the defense missile trajectory and the sphere defined by the hit altitude, is introduced. Then the motion of the virtual impact point caused by the external acceleration applied to the missile is derived. The proposed guidance algorithm generates the acceleration command that moves the VIP to the PIP along the shortest path without any iterative procedure and has high potential as an onboard midcourse guidance algorithm. The validity of the proposed guidance algorithm has been demonstrated through the case study.